Teaching business ethics post GFC: A corporate social responsibility of universities - Issa, Theodora; Pick, D. (2016)
© 2017 by IGI Global. All rights reserved.Following the recent downfall of several high ranking executives, not only in the business world, but also in governments, attention is directed to the teaching of ethics in business schools. More specifically attention is drawn to these schools' purposes, values, methods, research, partnerships and dialogues in terms of their responsibilities regarding management education. In the current academic environment business ethics are recognized as an important element in curriculum, but these topics have not yet become fully and successfully embedded in the mainstream business education. Consequently, business schools worldwide are adapting their curricula, research, teaching methodologies and institutional strategies to become better aligned with new challenges and opportunities. However, there is a need for research that will provide theoretical underpinnings for such changes to curricula in terms of pedagogy and content. This chapter examines a method of teaching business ethics. The results of this research were conducted on undergraduate students in their final year study.